More on Prices vs. Quantities - Laffont, Jean Jacques (Review of Economic Studies, 1977)
Journal Article More on Prices vs. Quantities Get access Jean Jacques Laffont Jean Jacques Laffont Laboratoire d'Econométrie de l'Ecole Polytechnique, Paris Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 44, Issue 1, February 1977, Pages 177–182, https://doi.org/10.2307/2296982 Published: 01 February 1977 Article history Received: 01 March 1975 Accepted: 01 August 1975 Published: 01 February 1977